Chemical parameters and microbial analysis of potable water of various tehsils in North Waziristan agency - Hussain, G. (International Digital Organization for Scientific Information, 2014)
Water samples were collected especially into sterile containers at three tehsilsi.eMiranshah, Shawaa and Mir aliin North Waziristan Agency. The water samples were immediately subjected to both chemical and microbiological analysis in order to evaluate the quality of potable water in circulation within the agency and identify its sources of contamination. Levels of iron, calcium and magnesium detectable in the circulating drinking water were far below the WHO recommended limits. Meanwhile, other microorganismslike E. coli, Coli form, were found absent. The pH of potable water in circulation falls within recommended limits (6.0-8.0). However, there were some parameters likeCa, Mg, Cl and ions like sulphate and bicarbonateions, which far exceed WHO standards. There is the need for adequate changes to be made at points where water distribution systems integrity appeared compromised. The people of the various tehsils are advised to boil water before drinking in order to avoid consumption of unwholesome biological agents in the water distribution networks. Â© IDOSI Publications, 2014.